2008
DOI: 10.1007/s10552-008-9244-4
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and the risk of Barrett’s esophagus

Abstract: Introduction-We examined the association between smoking and the risk of Barrett's esophagus (BE), a metaplastic precursor to esophageal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 30 publications
3
41
1
Order By: Relevance
“…This difference in strength of the associations with BE and esophageal adenocarcinoma is consistent with the literature (e.g., refs. 9,12,16,42,43). This observation may indicate that smoking plays a role in the later stages of esophageal carcinogenesis: in the progression of BE to esophageal …”
Section: Cigarette Smokingmentioning
confidence: 89%
See 2 more Smart Citations
“…This difference in strength of the associations with BE and esophageal adenocarcinoma is consistent with the literature (e.g., refs. 9,12,16,42,43). This observation may indicate that smoking plays a role in the later stages of esophageal carcinogenesis: in the progression of BE to esophageal …”
Section: Cigarette Smokingmentioning
confidence: 89%
“…Two casecontrol studies have found comparable results (12,16). One possible explanation is that former smokers have more health-seeking behavior and may therefore be more likely to be diagnosed with BE.…”
Section: Cigarette Smokingmentioning
confidence: 94%
See 1 more Smart Citation
“…By relaxing the lower esophageal sphincter and interfering with esophageal peristalsis, calcium antagonists and other muscle-relaxing agents promote acid reflux. Although all these relationships may be influential in individual patients, the overall epidemiologic relevance of dietary patterns, social habits, and drug consumption seems relatively small [35,36,37]. They do not to account for the general geographic or temporal patterns of GERD, as well as its various grades of severity among individual patients.…”
Section: Associations With Food Drugs and Social Habitsmentioning
confidence: 99%
“…Studies on the pathogenetic role of tobacco (45) and alcohol yield conflictive results, and an association with BE is only found in some of them (46,47). Vegetable-and fruit-rich diets have been associated with a lower BE risk attributed to high antioxidant levels (48).…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%